Detection of DNA of Leishmania siamensis in Sergentomyia (Neophlebotomus) iyengari (Diptera: Psychodidae) and Molecular Identification of Blood Meals of Sand Flies in an Affected Area, Southern Thailand. Issue 5 (24th April 2018) - Siripattanapipong, Suradej; Leelayoova, Saovanee; Ninsaeng, Ubolrat; Mungthin, Mathirut
Abstract: In Thailand, leishmaniasis is an emerging vector-borne disease that has become a public health concern. In related epidemiological surveys to identify potential Leishmania vectors in the affected areas, DNA of Leishmania martiniquensis (Kinetoplastida: Trypanosomatidae) was detected in Sergentomyia ( Neophebotomus ) gemmea (Diptera: Psychodidae) and Sergentomyia ( Parrotomyia ) barraudi (Diptera: Psychodidae). Recently, a more elaborate study was conducted in the same areas that included sand fly species identification, screening sand flies for the presence of Leishmania DNA and blood meal analysis to identify potential reservoir hosts directed toward assessing the risk of human infection. Twenty-nine archived pools of sand flies collected in Hat Samran District, Trang Province were used in this study. Sand fly species were confirmed using PCR encompassing regions within the mitochondrial DNA. Leishmania DNA was detected using PCR of the heat shock protein 70 region ( hsp 70-PCR) and blood meal identification was performed using PCR of the cyt b gene of vertebrate mitochondrial DNA ( cytb -nd1-PCR) and human-specific AluYb8 repeat (AluYb8-PCR). Four sand fly species were confirmed, i.e., Phlebotomus ( Anaphlebotomus ) stantoni (Diptera: Psychodidae), S. barraudi, Sergentomyia ( Neophlebotomus ) iyengari (Diptera: Psychodidae), and S. gemmea. Leishmania siamensis was detected in one female S. iyengari . Only human blood was detected in P. stantoni and S. gemmea, while both sun skink ( Mabuya multifasciata ) and human blood were detected in S. iyengari . In this study, we showed that S. iyengari could be a potential vector of L. siamensis infection among humans.